Are Drinking Motives Universal? Characteristics of Motive Types in Alcohol-Dependent Men from Two Diverse Populations - Ertl, Verena; Preuße, Melissa; Neuner, Frank (Frontiers in Psychiatry, 2018)
Since alcohol use disorders are among the most prevalent and destructive mental disorders, it is critical to address factors contributing to their development and maintenance. Drinking motives are relevant driving factors for consumption. Identifying groups of drinkers with similar motivations may help to specialize intervention components and make treatment more effective and efficient. We aimed to identify and describe distinct motive-types of drinkers in dependent males from two diverse cultures (Uganda and Germany) and to explore potential differences and similarities in addiction-related measures. Moreover, we investigated specific links between motive-types and childhood maltreatment, traumatic experiences and symptoms of comorbid psychopathologies. In order to determine distinct drinking motive-types, we conducted latent class analyses concerning drinking motives (Drinking Motive Scale; DMS) in samples of treatment-seeking alcohol-dependent men (N = 75). Subsequently we compared the identified motive-types concerning their alcohol-consumption and alcohol-related symptoms (Alcohol Use Disorders Identification Test; AUDIT), history of childhood maltreatment (Childhood Trauma Questionnaire; CTQ), trauma exposure (Violence, War and Abduction Exposure Scale; VWAES), psychopathology (Posttraumatic Stress Diagnostic Scale; PDS, Depression-section of the Hopkins Symptom Checklist; DHSCL and Brief Symptom Inventory; BSI) and deficits in emotion regulation (Difficulties in Emotion Regulation Scale; DERS). We found two congruent drinking motive-types in both contexts. Reward-oriented drinking motives like the generation of positive feelings and enhancing performance were endorsed almost equally by both motive-types, whereas high relief-motive-endorsement characterized one group, but not the other. The relief-motive-type drank to overcome aversive feelings, withdrawal, and daily hassles, and was characterized by higher adversity in general. Emotional maltreatment in childhood and psychopathological symptoms were reported to a significantly greater extent by relief-drinkers (effect sizes of comparisons ranging from r=.25 to r=.48). However, the motive-types did not differ significantly on alcohol-consumption or alcohol-related symptoms and traumatic experiences apart from childhood maltreatment. The chronology of addiction development and patterns of drinking motivation seem to be similar across cultures, i.e. that motive-targeting interventions might be applicable cross-culturally. Addressing comorbid symptomatology should be a key treatment component for relief-drinkers, whereas finding alternatives for the creation of positive feelings and ways to counteract boredom and inactivity should be a general treatment element.